2018
DOI: 10.1186/s40658-018-0207-x
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with a SiPM-based PET/CT scanner: influence of acquisition time on image quality

Abstract: BackgroundA newly introduced PET/CT scanner (Discovery Meaningful Insights—DMI, GE Healthcare) includes the silicon photomultiplier (SiPM) with time-of-flight (TOF) technology first used in the GE SIGNA PET/MRI. In this study, we investigated the impact of various acquisition times on image quality using this SiPM-based PET/CT.MethodsWe reviewed data from 58 participants with cancer who were scanned using the DMI PET/CT scanner. The administered dosages ranged 295.3–429.9 MBq (mean ± SD 356.3 ± 37.4) and imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 19 publications
4
48
0
Order By: Relevance
“…As expected, a reduction of emission time led to an increase in image noise, which is in line with prior studies by van Sluis et al [11] and Sonni et al [23]. An in-depth overview of image noise across all employed reconstruction algorithms is provided in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, a reduction of emission time led to an increase in image noise, which is in line with prior studies by van Sluis et al [11] and Sonni et al [23]. An in-depth overview of image noise across all employed reconstruction algorithms is provided in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…It is well known that, the 18 F-FDG uptake of small structures in PET is underestimated due to the important partial-volume-effects (PVE), affecting the emission signal recovery from these structures [6][7][8] . Spatial resolution, system sensitivity and image contrast in PET/CT have improved due to recently introduced solid-state digital PET/CT (dPET) [9][10][11] . A recent study has shown that Siemens Biograph Vision dPET has a 3.7 mm spatial resolution (vs 4.3 mm for Biograph mCT Flow cPET), and a 70.3% increased sensitivity compared to precedent Biograph mCT Flow cPET 11 .…”
mentioning
confidence: 99%
“…[ 18 F]FDG PET image quality decreases with weight and enlarging body habitus on digital and analogic PET/CT imposing further optimization and harmonization also in digital PET/CT. This is important for clinical routine, but also (multicentric) research and development of arti cial intelligence software.…”
Section: Resultsmentioning
confidence: 99%
“…However little has been described about the necessity and modalities of these compensatory techniques in dPET/CT. Positive in uence of acquisition time on PET IQ in dPET/CT has been reported in 58 oncologic patients [18] Our primary goal was characterizing on digital PET/CT the relation between patient's body mass index (BMI), weight, fatty mass (FM) and [ 18 F]FDG PET image quality, as an important rst step towards optimizing and harmonizing imaging protocols in digital PET/CT.…”
Section: Introductionmentioning
confidence: 99%